Optimization of hemolysin formation in Alcaligenes species isolated from abattoir wastewater samples in Akure, Ondo State, Nigeria: DOI: 10.48129/kjs.9406 - Olusola-Makinde, Olubukola Olayemi; Arotupin, Daniel Juwon; Okoh, Anthony Ifeanyi (Kuwait Journal of Science, 2022)
The function of haemolysin is significant during infections, it can also act as toxin; therefore, it has been used as molecular marker for pathogenicity. This study evaluated conditions for optimal haemolysin production by Alcaligenes faecalis strains isolated from a city abattoir wastewater. The conditions investigated for haemolysin production were size of the inoculum, initial pH of production medium, bacterial incubation temperature, agitation speed, and growth media. Thereafter, the effects by various treatments on the haemolytic activity of the produced haemolysin were assessed. The genus Alcaligenes was assigned to the test organisms after analysis of their 16S rRNA gene sequence with accession numbers: MF498824, MF498825 and MF498827 accordingly. Optimum conditions for haemolysin production for Alcaligenes faecalis strain OS42 were inoculum size 0.5% (v/v), pH 9, 20 oC, 0 rpm and brain heart infusion broth. Then, 77% and 79% haemolytic activities were attained at 20 h for strains OS42 and OS61 respectively. Cholesterol and EDTA did not affect crude haemolysin production. This work revealed haemolysin production by Alcaligenes strains sourced from abattoir wastewater effluent, and demonstrated that this effluent is contaminated with pathogenic Alcaligenes strains. This is a public health risk due to their prospective to cause human and animal infections.